Effects of ibuprofen on plasma endothelin levels and some vital parameters during endotoxin shock in rabbits - Vural, P; Canbaz, M; Akbulut, A; Celik, I (Elsevier, 2002)
Background: There is evidence that septic shock results from breakdown in the balance between vasodilators such as prostacyclin, prostaglandin E-2, and nitric oxide, and the vasoconstrictors thromboxane A(2), serotonin, and endothelin. Increased plasma endothelin (ET) concentrations during septic shock were found. Inducing phospholipase A2, ET causes release of arachidonic acid and production of prostaglandins. Ibuprofen is nonsteroidal anti-inflammatory drug inhibiting prostaglandin synthesis. There are no any information about the effects of ibuprofen on ET production in endotoxemia. In the present study we aimed to determine the effects of ibuprofen on plasma ET concentrations in an animal model of endotoxin shock. Methods: A total of 28 rabbits were randomly allocated into four groups. The first group only received saline and served as controls. The rest of the animals (groups 2, 3, and 4) were injected intravenously with endotoxin at a dose of 2 mg/kg. To the third group, ibuprofen at 30 mg/kg dosage was given, 30 min following endotoxin administration, whereas in the fourth group animals, ibuprofen was administered 30 min before endotoxin administration. Animals were monitored through the canulation of femoral arteries and venules under the complete anaesthesia. At 0, 30, 60, 90, 120, 180, and 240 min, arterial blood pressure, heart rate, and ET determinations were carried out. Results: Ibuprofen before the endotoxin administration was more effective in controlling the increase in heart rate. Ibuprofen was also effective in inhibiting the sudden reductions in blood pressure if administered before endotoxin. However, if administered after endotoxin injection, ibuprofen precipitated the reduction in blood pressure further. Ibuprofen reduced the ET production which was induced by the endotoxin administration. Conclusions: Ibuprofen administration during endotoxin shock seems to decrease the elevated ET concentrations, and increase the blood pressure. (C) 2002 Elsevier Science B.V. All rights reserved.
Keywords: ibuprofen; plasma endothelin; rabbits